2012
DOI: 10.1002/oti.1333
|View full text |Cite
|
Sign up to set email alerts
|

Activities with Higher Influence on Quality of Life in Older Adults in Japan

Abstract: The present study aimed to investigate the influence of 10 activities on quality of life (QOL) in Japanese older adults and to verify which activities had higher influence on QOL level. The subjects were 465 Japanese community-dwelling older adults. QOL was assessed by the brief version of the World Health Organization Quality of Life (WHOQOL-BREF) and the complementary assessment to measure the QOL of older adults (WHOQOL-OLD) module. Activity and participation were measured through a questionnaire concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
4
23
0
1
Order By: Relevance
“…We also found that social leisure activities, especially use of media, religious activity, sports and outdoor leisure activity and hobby and other leisure activity were the strongest predictors of quality of life. This is consistent with a similar study conducted in Japan; it was found that the leisure activity with the highest influence on quality of life was social activity followed by reading and writing (Sampaio et al, ). Also, our result that physical functioning significantly predicted quality of life was consistent with the results of a Hong Kong‐based study (ß = 1.064, p < 0.05) (Cheung et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that social leisure activities, especially use of media, religious activity, sports and outdoor leisure activity and hobby and other leisure activity were the strongest predictors of quality of life. This is consistent with a similar study conducted in Japan; it was found that the leisure activity with the highest influence on quality of life was social activity followed by reading and writing (Sampaio et al, ). Also, our result that physical functioning significantly predicted quality of life was consistent with the results of a Hong Kong‐based study (ß = 1.064, p < 0.05) (Cheung et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The presented study found that increase in physical activity significantly improved the QOL of older adults. Gill et al found that a higher level of physical activity determines the QOL [34] and acts as its protective factor [35]. Interventions aimed at increased activity of older adults affect their QOL positively.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because reading is necessary for performing many daily tasks and achieving a number of common societal objectives (i.e., daily living, social interaction, recreation, and work), reading difficulty can cause substantial disability (defined as reduced ability compared to the norm to perform reading tasks that are important to an individual), and can be detrimental to quality of life (QOL). [2][3][4][5] Previous studies that have evaluated reading in subjects with visual impairment almost exclusively have attributed reading disability to visual acuity (VA) loss due to refractive error, cataract, or macular disease. [6][7][8] Therefore, there exists a common assumption (backed by some evidence) that reading is not affected in diseases of peripheral vision loss, such as glaucoma, especially when VA is normal.…”
mentioning
confidence: 99%